PENDEKATAN MATEMATIS DALAM MENGIDENTIFIKASI RENDAHNYA PEMAHAMAN PESERTA DIDIK DALAM MANAJEMEN WAKTU - nursupiamin nursupiamin (Kelola: Journal of Islamic Education Management, 2019)
Technology not only has a positive impact on its users, it also shows negative impacts that cannot be underestimated. One of the negative impacts is time management. Time management plays an important role in the learning success of students. Time management plays an important role in the learning success of students. In this study, the authors take a mathematical approach in identifying poor understanding of students about time management. The type of approach used is library research with the method of collecting data using documentation to be analyzed through content analysis techniques. The results of the study show that poor understanding of students in time management can be identified through mathematical approaches such as numerical methods, with stages: (1) Determination of design or research model; (2) Searching for primary data, i.e. the texts themselves; and (3) Search for contextual knowledge. This study begins with quantitative data analysis. Data obtained through time management questionnaires and learning outcomes tests. In descriptive statistical analysis obtained a description of the average score. While inferential statistical analysis is intended for hypothesis testing and regression testing. Next is the implementation of numerical methods in identifying poor understanding of students about time management.  At the end of the results of the study conducted a qualitative analysis phase. The findings of different researchers are likely to be different because they can be influenced by the location or individual characteristics of students.